PRACTICAL INNOVATION ON ELEOCHARIS DULCIS WASTE-BASED COMPOST FERTILIZER BY PT PUPUK ISKANDAR MUDA IN GAMPONG BLANG ME - Jufri; Mulyawan, Rizka; Zufina, Rezki; Alfriyanto, Mochammad Bimo; Fikri, Ahmad; Rahman, Aulia (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Training on the use of dried and dead Purun plants as compost fertilizer raw material was carried out by PT Pupuk Iskandar Muda. The participants of the conducted training were from small enterprises in Gampong Blang Me, UMKM Beujroh. The practice was aimed to improve the community’s knowledge, awareness and action changes towards dead and dried Purun plants. The training was implemented by showing and involving the participants in composting dried Purun plants. After the activity, it was found out that development in knowledge, awareness and action of participants. Training participants’ knowledge of composting dried Purun plant with one hundred percent rise. Moreover, their awareness of negative potential from dried Purun plant also increase by ninety percent. Lastly, the community commitment to implement the procedure was also raised from zero to ninety percent of the participants involved. Besides, the training affected the community positively by utilizing dead dried Purun plant into compost with other affirmative aspects such as women empowerment and potential income generation.